A Systematic Literature Review of Development Models for Local Wisdom-Integrated Science Learning in Nusa Tenggara, Indonesia - Syarful Annam; Amalia Syuzita; Rosi Pratiwi; Yusuf Sarkingobir (CV. Institute of Multidisciplinary Research and Community Service (CV. IMRECS)), 2024)
Abstract: This study explores trends in the design and implementation of research and development (RD) models tailored for science education rooted in local wisdom within the Nusa Tenggara region (NTB and NTT), Indonesia. Utilizing a Systematic Literature Review (SLR) methodology, the research synthesizes findings from 20 pertinent articles published between 2017 and 2023, adhering to specific inclusion and exclusion criteria. Selected studies are indexed in SINTA (levels 1–6) and focus on ethnoscience, local wisdom, and RD models, while studies outside primary and secondary school science education or predating 2017 were excluded. The review identifies ADDIE (Analyze, Design, Develop, Implement, Evaluate) and 4D (Define, Design, Develop, Disseminate) as the most frequently employed development models, each representing 40% of the analyzed studies. Their popularity stems from their structured processes and adaptability to tight development timelines. Less commonly used models, such as Borg Gall and Dick Carey, feature in only 10% of cases, likely due to their complexity and resource demands. Most studies focus on producing contextually relevant teaching materials, such as ethnoscience-based modules, interactive tools, and multimedia resources that incorporate elements of local wisdom. The integration of local cultural knowledge into science learning enhances students' understanding of abstract scientific concepts, cultivates critical thinking, and strengthens cultural appreciation. These findings emphasize the value of culturally responsive approaches in designing science education materials that connect traditional wisdom with contemporary scientific perspectives. In summary, the ADDIE and 4D models are pivotal in fostering culturally relevant science education in Nusa Tenggara. Their practical and systematic frameworks enable the effective integration of regional culture into science curricula, supporting the creation of impactful and contextually aligned educational practices. Keywords: science learning, local wisdom, ethnoscience, ADDIE model, 4D model, Nusa Tenggara, systematic literature review.